EFFECT OF GREEN MANURE APPLICATION ON SOIL FERTILITY, GROWTH, DEVELOPMENT AND YIELD OF COTTON IN TYPICAL SANDY LOAM SEROZEM SOIL CONDITIONS OF UZBEKISTAN - Halmanov, Nurali T. (International Journal of Psychosocial Rehabilitation, 2020)
. It is discussed on effect of green manure application on changes of agro physical and agrochemical properties of serozem soils of Zaravshon walley of Uzbekistan. Several varieties of field crops such as typhoon, pea, and rye were used as a green manure. Field and laboratory investigations showed an improvement of physical, chemical and biological soil properties, as well as on better growth, development and yield of cotton plants under influence of green manure.